Bovine colostrum derived-exosomes prevent dextran sulfate sodium-induced intestinal colitis via suppression of inflammation and oxidative stress. (22nd March 2022) - Han, Geonhee; Cho, Haeun; Kim, Hyosuk; Jang, Yeongji; Jang, Hochung; Kim, Da Eun; Kim, Eun Sun; Kim, Eun Hye; Hwang, Kwang Yeon; Kim, Kwangmeyung; Yang, Yoosoo; Kim, Sun Hwa
Abstract : Colostrum-derived exosomes have a preventive effect on colonic colitis caused by inflammatory bowel disease. Abstract : Despite the rise in the global burden of inflammatory bowel disease, there is a lack of safe and effective therapies that can meet the needs of clinical patients. In this study, we investigated the beneficial effects of bovine milk, especially colostrum-derived exosomes (Col-exo) in a murine model of ulcerative colitis induced by dextran sodium sulfate (DSS). Col-exo activated the proliferation of colonic epithelial cells and macrophages, and created an environment to relieve inflammation by effectively removing reactive oxygen species and regulating the expression of immune cytokines. Besides, Col-exo could pass through the gastrointestinal tract intact and efficiently deliver bioactive cargoes to the stomach, small intestine, and colon. Our results showed that oral gavage of Col-exo can alleviate colitis symptoms including weight loss, gastrointestinal bleeding, and chronic diarrhea by modulating intestinal inflammatory immune responses. Overall, bovine colostrum-derived exosomes with excellent structural and functional stability may offer great potential as natural therapeutics for the recovery of colitis.